A BLUEPRINT TO AUDITING ACCOUNTANT SERVICES QUALITY - Valdivia Ramos, Román Arturo (2014)
The question I asked myself was some time ago ...... “Who audits the accounting service or accounting staff ?”. This has been the trigger to make this re-search work. The accountant, accountant technician, bookkeeper, accounting assistant and many others working in an accounting department, we believe that doing their job properly, they have regulations and very clear and precise procedures to follow. But who makes you follow the accounting staff about their work, to know or meet, if truly compliance with the rules, the processes, procedures, and troubleshooting errors with feedback, the analysis difference, as well as accounting standards, among others.Sincerely believe that few organizations, companies and institutions that carry out an audit of quality accounting service.Accounting staff, bookkeeper or assistant, is evaluated by its results which are reflected in the reports, EE.FF., and other documents that are needed for decision-ma-king in any organization.But was perhaps the accounting staff is not free of errors, faults, slips or others? Certainly you do!